(untitled) (Chemical Bulletin of Kazakh National University, 2023)
Pesticides are one of the largest groups of environmental pollutants used to protect agricultural plants from different pests and weeds. Soil is the initial area of accumulation of pesticides after their release into the environment. Determination of pesticides in soil is complicated by matrix effects and laborious sample preparation which generally involves the use of large amounts of organic solvents. Development of accurate green analytical methods for determination of pesticides in soil is an urgent task in environmental and analytical chemistry. In this study a method based on vacuum-assisted headspace solid-phase microextraction (Vac-HSSPME) coupled with gas chromatography-mass-spectrometry (GC-MS) was developed for the quantification of nitrogen-containing pesticides in soil samples. The pesticides atraton, simazine, atrazine, propazine, diazinon, metribuzin, prometryn, and oxyfluorfen were target analytes. The effects of water addition, reduced pressure, salting-out and pH adjustment on the extraction efficiency of target pesticides from soil were studied. Using Vac-HSSPME, the increase in the responses for all target pesticides by 3-7 times compared to ambient-pressure HSSPME was observed. Addition of water resulted in 2 to 380 times increase of the peak areas of analytes obtained using Vac-HSSPME. Optimum Vac-HSSPME performance was achieved using 60 min extraction at 60 °C. The proposed method can be recommended for quantification of atraton, atrazine, propazine, diazinon, prometryn, and oxyfluorfen in soil. Under optimum conditions the weighted linear regressions with R2 > 0.949 were obtained for most analytes in the concentration range 25-200 ng/g. The limits of detection and quantification ranged from 0.1 to 4 ng/g, and from 0.4 to 12 ng/g, respectively.